Rapamycin-ameliorated diabetic symptoms involved in increasing adiponectin expression in diabetic mice on a high-fat diet - Fang-Hua Gong; Yan-Na Ye; Jin-Meng Li; Hai-Yang Zhao; Xiao-Kun Li (Kaohsiung Journal of Medical Sciences, 2017)
Recent studies showed that rapamycin improved diabetic complications. Here, we investigated the metabolic effects of rapamycin in type 2 diabetes model (T2DM) mice. Mice were treated with a daily intraperitoneal injection of rapamycin at 2 mg/kg or vehicle only for 3 weeks and were maintained on a high-fat diet. The treated diabetic mice exhibited decreased body weight, blood glucose levels, and fat mass. FGF21 expression was suppressed in C57B/L6 mice, but adiponectin expression increased both in FGF21 KO and C57B/L6 mice. These results suggest that rapamycin may alleviate FGF21 resistance in mice on a high-fat diet. The reduction of adipose tissue mass of the diabetic mice may be due to the increased adiponectin.